Dakwah Melalui Internet: Kajian tentang Manajemen Penyebaran Informasi dalam Dakwah - Sukayat, Tata (Prophetica, 2009)
Liabilities preaches have no spatial limitation and time. Whenever and wherever mission shall continually be performed. Most more at technological upturned era information, Internet facility with to amount to excess it as ability it to feature multiple diverse information and consumers its that reaches multiethnic and religion. Mission via Internet will so strategic to introduce Islam, removing misconception about Islam and to word face to face Islam teaching to opposing and gets across Islam. Keywords:Dakwah, Informasi, Internet